Edukasi Kesehatan Reproduksi Remaja Di Karangtaruna Pendowohardjo - Pri Hastuti; Desi Ekawati (Lontara Abdimas : Jurnal Pengabdian Kepada Masyarakat, 2021)
Adolescence is the initial period of maturity of the reproductive organs in humans or the so-calledpuberty. Based on previous preliminary studies, adolescents prefer sources of reproductive health informationobtained from peers and parents, but if this is not given an explanation from health workers directly it will causedifferent perceptions from each teenager which can cause gaps. Based on the preliminary study, researchers areinterested in doing community service with the title "Adolescent Reproductive Health Education in KarangtarunaPendowohardjo". The purpose of this research is to increase the knowledge of adolescents about the importanceof reproductive health from a physical and psychological perspective. Adolescent Reproductive Health EducationActivities at Karangtaruna Pendowohardjo were carried out using counseling and demonstration methods, themedia used using teaching aids. The target audience in this community service is Youth, especially YouthOrganizations in Pendowohardjo Sewon Bantul with a target number of 48 Youth Youth Organizations. The resultsof this research are that adolescents gain knowledge and skills regarding Reproductive Health through counselingand demonstrations.